KARAKTERISTIK IBU-IBU WIRAUSAHA DI KOTA MADIUN DAN PENGARUHNYA TERHADAP MOTIVASI BERWIRAUSAHA - Widdy Tri Prasetyo, Vinsensius (Widya Warta, 2018)
The purpose of this research was to identify the characteristics of entrepreneurial housewives in the city of Madiun and its effects on the motivation of entrepreneurship. The samples taken were 120 respondents. The technique of data collection was by giving questionnaire to the housewives running their business in the city of Madiun. The techniques of data collection were descriptive and multiple linear regression. The result showed that housewives running their business have different characteristics; they are different in terms of their age, their time spent for their business, their average turnover per month, their education, their husbands’ jobs, their number of family members, and their average expenditure for basic needs each month. Some of the charactristics affected housewives’ motivation in entrepreneurship; they were their education, their husbands’ jobs,   mothers to berwirausaha is education, and their average expenditure for basic needs each month. The other caharacteristics, namely their age, their time spent for their business,  their average turnover per month, and their number of family members, did not significantly affect housewives’ motivation in entrepreneurship.